2018
DOI: 10.1161/circheartfailure.117.004397
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanical Unloading by Total Support of Impella in Myocardial Infarction Reduces Infarct Size, Preserves Left Ventricular Function, and Prevents Subsequent Heart Failure in Dogs

Abstract: LV mechanical unloading by the total support of Impella during the acute phase of myocardial infarction reduced infarct size and prevented subsequent heart failure in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 32 publications
1
66
0
1
Order By: Relevance
“…The effects of ventricular unloading on infarct scar size extend beyond cardioprotective signaling. Clinical and preclinical data have demonstrated that acute unloading decreases ventricular wall stress, an expected outcome resulting from pressure and volume unloading [ 47 , 64 , 66 , 73 – 75 ]. Early critical work conducted in the 1970s and 1980s linked acutely increased wall stress and filling pressures with the disruption of connective tissue within the heart [ 76 79 ].…”
Section: Acute Cardiac Unloading and I-r Injurymentioning
confidence: 99%
“…The effects of ventricular unloading on infarct scar size extend beyond cardioprotective signaling. Clinical and preclinical data have demonstrated that acute unloading decreases ventricular wall stress, an expected outcome resulting from pressure and volume unloading [ 47 , 64 , 66 , 73 – 75 ]. Early critical work conducted in the 1970s and 1980s linked acutely increased wall stress and filling pressures with the disruption of connective tissue within the heart [ 76 79 ].…”
Section: Acute Cardiac Unloading and I-r Injurymentioning
confidence: 99%
“…In their elegant study, the authors induced AMI in 20 canine models by occluding the left anterior descending coronary artery for 180 minutes followed by 60 minutes of reperfusion. 30 The animals were then divided into three groups: a control group (no LV support), partial unloading group (Impella CP flow increased until arterial pulse pressure was reduced by 50%), and total unloading group (Impella CP flow increased until the arterial waveform was nonpulsatile). In the supported groups, the Impella CP was turned on 60 minutes after the onset of ischemia and continued for 60 minutes after reperfusion.…”
Section: Unloading-pre Clinical Datamentioning
confidence: 99%
“…These findings suggested for the first time that first unloading the LV and delaying coronary reperfusion may significantly reduce myocardial infarct size compared with primary reperfusion alone. However, several questions remained unanswered: (1) what were the long-term effects of primary unloading on LV scar size and LV function, (2) how important was the delay to reperfusion and was 60 minutes required, and (3) was SDF1a an innocent bystander or did it play a functional role in the cardioprotective effects of primary unloading 26 ?…”
Section: Preclinical Studies On Left Ventricular Unloadingmentioning
confidence: 99%